An unusual presentation of non-IBD related colorectal primary extranodal diffuse large B cell lymphoma with a colo-colonic fistula - Rima Nakrani; Ho-Man Yeung; Matan Arnon; Alexandra Selby; Christine Burgert-Lon; Bhishak Kamat (Greater Baltimore Medical Center, 2021)
Diffuse large B cell lymphoma of the sigmoid colon and rectum is relatively uncommon and aggressive. Due to its nonspecific symptomatology, patients are often diagnosed late into the disease and present with life-threatening complications, such as hemorrhage, obstruction, or perforation, requiring emergent surgical intervention. Patients with colorectal lymphoma typically have inflammatory bowel disease or immunosuppression. We present a case of a 79-year-old male with no known inflammatory bowel disease or immunosuppression, who had significant weight loss, diarrhea, and abdominal fullness, found by CT to have irregular wall thickening of the recto-sigmoid colon along with a colo-colonic fistula, concerning for bowel perforation. Endoscopic evaluation and biopsy confirmed the diagnosis of recto-sigmoid Diffuse large B cell lymphoma, with a PET/CT scan revealing stage IV disease. He had a partial response to six cycles of palliative reduced dose R-CHOP and is currently receiving palliative radiation to the sigmoid colon and rectum. Surgery and/or chemoradiation remain the mainstay therapy for this condition. Clinicians, however, must consider patient's functional, nutritional, and clinical status prior to choosing an optimal therapeutic regimen. This case illustrates a unique clinical presentation of this condition and the associated diagnostic and therapeutic challenges that arise in order to prevent life-threatening complications.